Kinerja dari Kepemimpinan, Lingkungan dan Disiplin Kerja Anggota Kepolisian Polres Karanganyar - Indah Dewi Yadyasen Ratna Sari; Istiatin Istiatin; Raisa A. Hamidah (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research aims to assess the impact of leadership, environment, and work discipline on the performance of members of the Karanganyar Police. It employs a descriptive quantitative research approach, utilizing purposive sampling for data collection. The analysis techniques utilized include classical assumption tests, multiple linear regression tests, hypothesis testing, and determination coefficients. Data processing was conducted using IDM SPSS Statistics 26. The findings indicate that leadership, environment, and work discipline positively influence the performance of Karanganyar Police members. The t-test results demonstrate that these factors significantly affect performance. Additionally, the F test results reveal that leadership, environment, and work discipline collectively have a significant impact on the performance variabels of the Karanganyar Police members. The R² test results show that these three factors account for 49.8% of the performance variabels, while the remaining 50.2% is attributed to other external variabels such as work stress, workload, motivation, communication, work culture, and others.